Piping Stress Analysis of XYZ Platform Using CAESAR II: Compliance Verification with ASME B31.3 - Mutadi Mutadi; Munaji Munaji (Mestro: Jurnal Teknik Mesin dan Elektro, 2026)
This paper presents the piping stress analysis of the XYZPlatform as part of the EPCI Contract for Platform Reactivation of the XYZ Project, operated by PT. XYZ. The analysis was conducted using CAESAR II Version 2019 (11.0) for piping system Model 03, covering the pipeline from Pig Receiver (R-002) to Upstream HIPPS (Z-010). The objective was to verify compliance with ASME B31.3 (2020) Process Piping code under various load cases including hydrotest, sustained, operating, occasional, and expansion conditions. Line properties analyzed involve 8-inch and 10-inch carbon steel pipes (A106 Grade B and API 5L X52) with design pressure up to 1,550 psi and design temperature of 200°F. Results demonstrate that all maximum stresses are within allowable limits, with sustained stress ratio reaching 60.8%, occasional stress ratio at 61.2%, and thermal expansion ratio at 23.0%. Maximum displacement in the operating condition is 9.013 mm in the X-axis direction, well within the 100 mm threshold. Flange leakage verification using the Pressure Equivalent Method yields a maximum ratio of 77.72%, confirming integrity. The minimum natural frequency of the piping system is 4.585 Hz, exceeding the required 4 Hz minimum. All equipment nozzle loads at the Pig Receiver are within allowable limits per CPY-SPE-0009. The study confirms that the proposed piping configuration for XYZPlatform is structurally sound and compliant with applicable codes and project specifications. Keywords: ASME B31.3; CAESAR II; XYZPlatform; XYZ Platform; Offshore Piping; Piping Stress Analysis